Development of a medication review tool for residents in Korean long-term care facilities - Kwanghee Jun; Soojin Lee; Ah young Lee; Young-Mi Ah; Ju-Yeun Lee (SAGE Publishing, 2022)
Introduction: Residents in long-term care facilities (LTCFs) are likely to suffer from drug-related problems, such as inappropriate polypharmacy and potential prescribing omissions due to multimorbidity and high-level frailty. Medication reviews are thus necessary to identify and resolve drug-related problems in LTCF residents. In this study, we aimed to develop a medication review tool for older adults in LTCFs in Korea. Methods: We did a systematic review to identify previously developed explicit criteria and devised preliminary potentially inappropriate medications (PIMs) list for the LTCF elderly from previous tools. Each item on this list was categorized into 23 underlying diseases/conditions, and the interventions necessary for each PIM were included. A two-round modified Delphi survey was performed sequentially for consensus evaluation of clinical appropriateness and feasibility of the list items by 12 experts (seven physicians in different specialties and five pharmacists specialized in geriatrics) and seven pharmacists, respectively. Results: We identified 22 existing tools and devised a preliminary PIM list including 100 items. Ninety-one items were derived from the two-round Delphi survey for clinical appropriateness. In the feasibility test, 77 items were integrated into the final medication review tool for the LTCF elderly. The final list was composed of items relating to PIMs in general (18), potential drug interactions (14), PIMs under specific diseases/conditions (26), a need for dose adjustment (2), and potential omissions (17). Conclusions: We developed a disease-category-based explicit medication review tool for detecting PIM use for LTCF residents. This tool may be helpful in implementing medication review practices to assist pharmacists or physicians for the elderly in LTCFs. Further research is required to validate the effectiveness of our tool in clinical practice.